Marketing Strategy of Griya iB Hasanah Financing Products: Evidence from the Bank Syariah Indonesia in Mataram - Hayati, Salwa; Susianti, Nurul; Azim, Muhammad Paozan (Maliki Islamic Economics Journal, 2021)
The purpose of this research is to find out the marketing strategy carried out and to find out the obstacles that occur in implementing the marketing strategy of the Griya iB Hasanah product at Bank Syariah Indonesia KC. Mataram. The research methodology used by the researcher a type of qualitative research using primary data sources and secondary data. The method of data collection, researchers used observation, interviews and documentations. The data analysis techniques used data reduction, data presentation and data conclusion drawing. As for the validity of the data using triangulation, peer assessment and adequacy of references. The results of the study indicate that the Islamic Bank of Indonesia Mataram branch office formulates in selecting and determining the target market by using the 4P marketing mix. How to improve the quality of human resources, in the process of serving customers, increasing promotional and outreach activities that place more emphasis on ASN, civil servants, and the general public, either by door to door, or by promoting through advertising in the form of banners and brochures, and down directly to the developer. Meanwhile, the obstacles that occur in implementing this strategy competition between sales from other banks and public perception of the mortgage financing mechanism at Bank Syariah Indonesia KC Mataram which is too complicated compared to other banks.